Synthesis of new 3,4-dihydropyrano[c]chromene derivatives and their evaluation as acetyl cholinesterase inhibitors - Bouazizi, Younes; Romdhane, Anis; Jannet, Hichem Ben (European Journal of Chemistry, 2014)
2-Amino-4-phenyl-4,5-dihydro-5-oxopyrano[2,3-c]chromen-3-carbonitrile derivatives (8a-d) have been isolated in good yields by the reaction of corresponding 4-hydroxycoumarin (1) with substituted aldehydes (2a-d) and malononitrile (3) under reflux conditions. The reactivity of α-functionalized iminoethers (9a-d) with hydrazine, hydroxylamine and piperidine was studied. The synthesized compounds were characterized by various techniques including spectroscopy. Compounds 8-11 were also evaluated as potential acetylcholinesterase inhibitors.